Policy responses to reduce the opportunity for horsemeat adulteration fraud: the case of the European Union - Kulas, Megan (Kansas State University, 2014)
Food production is changing in response to an expanding global population. The ability to distribute and process ingredients amongst many individuals and countries has brought economic benefits while also creating new problems. By increasing the complexity of the supply chain, the food industry has birthed new dynamics, thus creating new opportunities for contamination, fraud, and other threats. One threat dynamic is the varying levels of food safety and quality control at different nodes along a supply chain. Contaminations pinpoint weaknesses of a supply chain, and such weaknesses could be exploited for harm. One way foods are intentionally contaminated is through food fraud. Food fraud involves substitution, mislabeling, dilution, and other means of criminal deception. Routine testing by an independent science-based group led to the discovery of one the largest scales of substitution and mislabeling in history—the 2013 adulteration of beef products with horsemeat. Commonly referred to as the horsemeat scandal of 2013, this important event in the history of the global food system affected several regions, hundreds of products, and thousands of retailers and consumers. To date, this scandal was one of the largest incidents of food fraud. Mostly based in the European Union, the horsemeat scandal prompted the European Commission to take regulatory action. The European Union’s policy response included the creation of a five-point plan that addresses the different facets associated with the scandal. The five-point plan sought to strengthen food fraud prevention; testing programs; horse passports; official control, implementation, penalties; and origin labelling. The five-point plan is intended to decrease the fraud opportunity for the adulteration of beef with horsemeat. According to the crime triangle, a concept frequently cited in the field of criminology, fraud opportunity has three main elements: the victims, the fraudsters, and the guardian and hurdle gaps. When any of these elements change, the opportunity for a fraudster to commit a crime also changes. The research question of this thesis explores the policy responses of the European Commission. The Commission’s five-point plan targets the three elements of fraud opportunity; therefore, future fraud opportunity for the adulteration of beef products with horsemeat will theoretically decrease.
Keywords: Food fraud; Food adulteration; European Commission; Horsemeat scandal; Food Science (0359); Public Policy and Social Welfare (0630)